Population and individual‐scale responses to patch size, isolation and quality in the hazel dormouse. Issue 9 (24th September 2014) - Mortelliti, Alessio; Sozio, Giulia; Driscoll, Don A.; Bani, Luciano; Boitani, Luigi; Lindenmayer, David B.
Abstract : Patch size, isolation and quality are key factors influencing species persistence in fragmented landscapes. However, we still lack a detailed understanding of how these variables exert their effects on populations inhabiting fragmented landscapes. At which ecological scale do they have an effect (e.g., individuals versus populations) and, on which demographic parameters? Answering these questions will identify the mechanisms that underlie population turnover rather than solely predicting it based on proxies (e.g., presence/absence data). We report the results of a large‐scale, three‐year study focused on the relative effects of patch size, isolation and quality on individuals and populations of an arboreal rodent, the hazel dormouse ( Muscardinus avellanarius ). We examined 30 sites nested within three landscapes characterized by contrasting levels of habitat amount and habitat quality (food resources). We quantified the effects of patch size and quality on the response of individuals (survival and litter size) and populations (density and colonization/extinction dynamics). We identified demographic mechanisms which led to population turnover. Habitat quality positively affected survival (not litter size) and population density (measured through an index). We infer that the decline in survival due to patch quality reduced patch recolonization rather than increasing extinction, while extinction was mainly affected by patch size. Our findings suggest that the effect of patch quality on individual and population parameters was constrained by the physical structure of the surrounding landscapes. At the same time, our results highlight the importance of preserving habitat quality to help the persistence of entire systems of patches.